Regulasi dan Sanksi Pelanggaran Iklan Televisi di Indonesia: Studi Kasus Iklan Garnier Micellar Water Tahun 2023 - Ahmad Ibrahim; Rizki Agus Nugraha; Denny Wahyudi; Daniel Handoko (Harmoni: Jurnal Ilmu Komunikasi dan Sosial, 2024)
Advertising is a crucial element in marketing strategies aimed at attracting consumer attention and influencing purchasing decisions. The rapid development of Indonesia's advertising industry, driven by increasing media consumption, has brought about ethical and regulatory challenges. This study examines the ethical violations in the Garnier Micellar Water television advertisement in 2023, which claimed to be the "No 1 Micellar Water in Indonesia" without sufficient evidence, violating the Indonesian Advertising Code of Ethics (EPI). Using a qualitative descriptive method, the research analyzes the content of the advertisement and interviews with advertising experts. Findings reveal that the claim was misleading, lacking valid data support, and driven by commercial pressures and insufficient ethical awareness. Recommendations include stricter enforcement of advertising ethics, enhanced awareness programs, and collaborative efforts among advertising industry stakeholders to uphold honesty and responsibility in advertising practices.